Exploring the Electronic Interactions of Adenine, Cytosine, and Guanine with Graphene: A DFT Study - Jawaher Qasem; Baliram Lone (ChemistryOpen)
Abstract This study has provided new insights into the interaction between graphene and DNA nucleobases (adenine, cytosine, and guanine). It compares how each nucleobase interacts with graphene, examining their selectivity and binding energy. The research also explores how these interactions impact the electronic properties of graphene, showing potential applications in graphene‐based biosensors and DNA sequencing technologies. Additionally, the findings suggest potential uses in DNA sensing and the functionalization of graphene for various biomedical applications. This study employs density functional theory (DFT) methods, utilizing the B3LYP functional with the 6‐311G basis set, to explore the electronic interactions between DNA nucleobases (adenine, cytosine, and guanine) with pure graphene (Gr). We investigate various properties, including adsorption energy, HOMO‐LUMO energy levels, charge transfer mechanisms, dipole moments, energy gaps, and density of states (DOS). Our findings indicate that cytosine interacts most favorably with graphene through its oxygen site (Gr‐Cyt‐O), exhibiting the strongest adsorption. Additionally, adenine's interaction significantly enhances its electronegativity and chemical potential, particularly at the nitrogen position, while decreasing its electrophilicity. Guanine, characterized by the smallest energy gap, demonstrates the highest conductivity among the nucleobases. These results suggest that graphene possesses advantageous properties as an adsorbent for guanine, highlighting its potential applications in biosensor technology.